Հայոց հարցի բալկանյան շրջադարձը (երկրաքաղաքական էտյուդ) - Շիրինյան, Լևոն (YSU Journal of International Affairs, 2015)
In World War I, each participating country had its own motivation. The Ottoman Empire, from the viewpoint of a deep understanding of the prevailinggeostrategic realities around him, which carefully concealed, had its own motivation. As a result of the Balkan wars, finally thrown out of Europe, and later, the ItalianTurkish War, banished from the Mediterranean region, the Ottoman Empire was trying to find its own center of the strategic balance in Minor Asia and in the Armenian Highlands. This led to the empire’s ambitions to destroy Armenia and Armenians. Russian reform program and contradictions of major powers on the Turkish issue intensified the formed trend. This is evidenced also the choice of Germany as an ally. The First World War gave the opportunity to do so. Thus, the Ottoman Empire entered the First World War to solve the Armenian question in the Turkish understanding. The idea of Armenocide and its execution has been a matter of time.
Keywords: the Balkans, Armenia, strategy, turning point